How soon can we identify at-risk patients: examining initial depressive symptomology and opioid use in musculoskeletal trauma survivors?. Issue 7 (July 2020) - Sharififar, Sharareh; Gupta, Sunny; Vincent, Heather K.; Vasilopoulos, Terrie; Zdziarski-Horodyski, Laura; Horodyski, MaryBeth; Hagen, Jennifer E.
Highlights: The study has shown that the severity of initial depressive symptoms and persistent opioid use at 6 weeks are two strong predictors of persistent depressive symptomology. Targeting the initial emotional response and the 6-week time point post-discharge may better represent patient responses to trauma and predict specific outcomes. The study has shifted the target date for classifying patients with orthopedic trauma into risk and protective clusters based on surveys conducted at in-hospital setting Abstract: Objectives: This study evaluates the associations between post injury depressive symptomology and opioid use from the initial time of injury in orthopedic trauma patients without pre-existing psychiatric conditions. Design and setting: This is a prospective study following the development of symptoms after orthopedic trauma injury conducted at a Level-1 trauma center. Patients: Orthopedic trauma patients (N=96; 43.4±16.5 yrs, 40.6% women) Main outcome measures and analysis methods: Beck Depression Inventory (BDI-II) was administered during index hospitalization and at 2-weeks, 6-weeks, and 3- months, and 6-months. In-hospital and out-patient opioid use were tracked. Regression analyses determined the relationship of opioid use and depressive symptoms during follow-up. Results: Twenty percent of patients had moderate depressive symptom levels (BDI 20-28 points) and 11% had severe depressive symptom levels (BDI ≥29) at the time of their index hospitalization. Inpatient BDI-II depressive symptom severity levels were significantly related to depressive symptomology at 2 -weeks, 6 -weeks, and 3 -months. In-hospital or discharge opioid dose was not associated with initial or persistent depressive symptomology. Patients with persistent opioid use at 6 weeks had higher depressive symptoms six months following post-discharge than those who ceased opioid use by 6 -weeks post-discharge. Conclusions: This study suggests that depressive symptomology immediately following musculoskeletal trauma is predictive for persistent depressive symptomology in a subset of our patient population. Inpatient BDI-II depressive symptom severity levels in the hospital were significantly related to BDI-II at 2-weeks, 6-weeks, and 3-months, and persistent opioid use, past 6-weeks, was independently associated with prolonged depressive symptomology as well. Further study into effective treatment and monitoring of mental health disturbances following trauma is needed, particularly in patients with continued need for and use of opioids after discharge.